2019
DOI: 10.26444/aaem/106224
|View full text |Cite
|
Sign up to set email alerts
|

Factors of work environment hazardous for health in opinions of employees working underground in the ‘Bogdanka’ coal mine

Abstract: Introduction. Employees performing work underground in coal mines are exposed to the effect of many hazardous factors in their work environment which negatively affect their health. Objective. The objective of the study was to recognize the opinions of employes working underground in one of the coal mines concerning the occurrence of factors hazardous for health in their work environment. Materials and method. The study was conducted in a group of 700 persons working underground in the 'Bogdanka' coal mine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Occupational exposure to extreme high temperature, as seen in industries such as steelmaking, tile production processes, mining, and rescuing, can lead to detrimental health effects (Lee et al., 2019). Especially, several studies showed that moisture and heat were the most commonly perceived adverse factors in the deep underground work environment (Liu et al., 2019; Strzemecka et al., 2019; Xie et al., 2020). Therefore, these studies have raised serious concerns about the impacts of extreme high temperature on occupational population health.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to extreme high temperature, as seen in industries such as steelmaking, tile production processes, mining, and rescuing, can lead to detrimental health effects (Lee et al., 2019). Especially, several studies showed that moisture and heat were the most commonly perceived adverse factors in the deep underground work environment (Liu et al., 2019; Strzemecka et al., 2019; Xie et al., 2020). Therefore, these studies have raised serious concerns about the impacts of extreme high temperature on occupational population health.…”
Section: Introductionmentioning
confidence: 99%
“…In coal mining activities, a range of occupational hazards including coal mine dust, exhaust gas, high temperature, high humidity, and noise form the coal mining environment ( 1 ). Respirable dust refers to dust particles with an aerodynamic diameter of less than 5 μm that can reach the deep respiratory tract and alveolar region, and the concentration of respirable dust directly affects the health of workers.…”
Section: Introductionmentioning
confidence: 99%
“…These might be the reasons behind the high and increasing annual rates of coal-mining occupational health problems such as lung diseases (pneumoconiosis and silicosis), cardiopulmonary function injury and cardiovascular disease among mining workers [ 7 , 8 , 9 , 10 ]. In addition, underground miners usually work in high-humidity and high-temperature environments, which present additional risks to the cardiopulmonary functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%